(3TQM GdeNJUQ GdcHjQ (B((3dYHO Gddg Hf YHOGdMce UGMH GdCeGe eGdc(B)s - (3CHi HcQ eMeO Hf YHO Gddg Hf eMeO Hf GdCHgQOis; (3YHO Gddg Hf YHO GdMces
(3ChdgG (B:s
(3bGd YHOGddg Hf GdMce bdJ deGdc CQGjJ GdCeI EPG hdOJ ef SjOgG s
(3Ydjg hbajI eDQNI SfI (B604(3g`s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B10 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs